Assistive Devices Used in Daily Living, User’s Satisfaction and Psychological Impact on the Devices of Persons with Mobility Disabilities - กองเกิด อภิญชาพัชญ์; โลหารชุน บุษกร; เทพมณฑา ปืนไทย; แก้วสว่าง สาริณี; โสลันดา ศุลีพันธ์ (Journal of Health Science of Thailand, 2024)
This survey study aimed at studying the use of assistive devices, user’s satisfaction with devices and services received from governmental sectors, and psychosocial impacts on the devices of persons with mobility disabilities. Altogether 418 participants were included from 10 provinces following the multistage sampling. A questionnaire, the Quebec user evaluation of satisfaction with assistive technology (QUEST 2.0) and the Psychological Impact of Assistive Devices Scale (PIADS) were administered. The results showed that the top-four assistive device types used by the participants were wheelchairs (60.77%) walking aids (46.41%) cushions (13.40) and lower limb prostheses (11.72%), respectively. The participants were quite satisfied with the assistive devices received from governmental sectors (mean 3.67, SD 0.77) as same as services (mean 3.59, SD 0.92). Weight, durability, and efficiency of the devices were at lower satisfaction level than other items of assistive device issues. Considering service issues, service system, repairs and maintenance services, and follow up were lower satisfaction level than other items. Additionally, 66.15% of the participants indicated that the assistive devices had positive psychological impact. 23.26% of those indicated that they had no impact. Other 10.60% of them specified that they had negative impact. Regarding different types of devices that the participants use, it showed that all of those had positive psychological impact on the tree sub-scores (competency, adaptability and self-esteem). The results may be taken into consideration for improving assistive device service system to response to user’s needs. Development of repair, maintenance and follow up services might support persons with disabilities to use assistive devices continuously and efficiently.